Openness and the Effects of Fiscal and Monetary Policies on Real Output in Nigeria (1960-2003) - Saibu, Olufemi Muibi (2015)
The study examined the effects of monetary and fiscal policies on the real output growth in the small open Nigerian economy. Specifically, it verified the implication of increasing economic openness on the efficacy of monetary and fiscal policy and also established whether fiscal and monetary policies had symmetrical effects on real output in Nigeria. This was with a view to establishing the validity of macroeconomic policy ineffectiveness proposition of new classical school in Nigeria.